Dynamic analysis and control of a three-revolute–prismatic–spherical parallel robot by algebraic parameters identification. (8th May 2019) - Ruiz-Hidalgo, NC; Blanco Ortega, A; Abúndez Pliego, A; Colin-Ocampo, J; Alcocer Rosado, WM
The inverse dynamic model of a three-revolute–prismatic–spherical parallel robot based on Lagrange method is presented. This parallel robot presents a different configuration in the orientation of the actuators of the already reported in the literature. The dynamic model is validated by simulations obtained with a virtual prototype under MSC Automatic Dynamic Analysis of Mechanical Systems environment. For positioning the moving platform in a desired orientation, a proportional–integral–derivative-type controller is implemented for trajectory tracking using the dynamic of the actuators. In this dynamic, the load supported is unknown, that is, due to the inclination of the moving platform, the weight is not evenly distributed. Algebraic identification of parameters is implemented in order to know the load and improve the response in the orientation of the moving platform. Some simulations were performed with the virtual prototype in co-simulation environment under MSC Automatic Dynamic Analysis of Mechanical Systems/View and MATLAB/Simulink to verify the performance of the proportional–integral–derivative controller using the algebraic parameters identification.